2014
DOI: 10.5334/ijic.1175
|View full text |Cite
|
Sign up to set email alerts
|

Care transitions for frail, older people from acute hospital wards within an integrated healthcare system in England: a qualitative case study

Abstract: Introduction: Frail older people experience frequent care transitions and an integrated healthcare system could reduce barriers to transitions between different settings. The study aimed to investigate care transitions of frail older people from acute hospital wards to community healthcare or community hospital wards, within a system that had vertically integrated acute hospital and community healthcare services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
133
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(144 citation statements)
references
References 44 publications
(87 reference statements)
7
133
0
4
Order By: Relevance
“…Previous studies have shown the importance of better continuity of care and of collaboration between health care providers to avoid gaps in the quality of taking care of the patients [1,3,4,29]. These results supports our results in that the new approach in the Executive inter-professional teamwork could change patients' everyday living situation in a positive direction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previous studies have shown the importance of better continuity of care and of collaboration between health care providers to avoid gaps in the quality of taking care of the patients [1,3,4,29]. These results supports our results in that the new approach in the Executive inter-professional teamwork could change patients' everyday living situation in a positive direction.…”
Section: Discussionsupporting
confidence: 90%
“…In this case the freedom led to further steps being taken way beyond the original project limitations, offering an integration of professional knowledge between team members. Interprofessional communication has been shown to increase the quality of care for frail older people [29]. This result is underpinned by Schaik et al [30] who, from a study with inter professional teams, draw the conclusion that organizational change often is chosen from the top but ideally should be chosen by the team to be respected and empowered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of the patient and informal caregiver can improve continuity of care, quality of care and positive experiences with care [9][10][11]. Therefore, it is important to use different perspectives (patient/professional/informal caregiver) in the evaluation of processes and outcomes on the level of health service delivery (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…alignment with patients' care needs; care coordination; team cooperation; and quality of care) [12]. However, few studies have evaluated multiple perspectives involved with changes in health service delivery [9,10,13].…”
Section: Introductionmentioning
confidence: 99%